2010
DOI: 10.1007/s12010-009-8893-4
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of Kraft Paper Mill Sludges to Ethanol by SSF and SSCF

Abstract: Paper mill sludge is a solid waste material composed of pulp residues and ash generated from pulping and paper making processes. The carbohydrate portion of the sludge has chemical and physical characteristics similar to pulp. Because of its high carbohydrate content and well-dispersed structure, the sludges can be biologically converted to value-added products without pretreatment. In this study, two different types of paper mill sludges, primary sludge and recycle sludge, were evaluated as a feedstock for bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 22 publications
4
51
0
12
Order By: Relevance
“…This yield was higher than that in previous report. 11) It has been reported that ethanol yields of 75-81% of the theoretical maximum were obtained from the SSF of kraft paper mill sludge, cellulase cocktail, and yeast. In contrast, no detectable amount of ethanol was produced without the addition of cellulase cocktail even after 72 h of fermentation (Supplemental Fig.…”
mentioning
confidence: 99%
“…This yield was higher than that in previous report. 11) It has been reported that ethanol yields of 75-81% of the theoretical maximum were obtained from the SSF of kraft paper mill sludge, cellulase cocktail, and yeast. In contrast, no detectable amount of ethanol was produced without the addition of cellulase cocktail even after 72 h of fermentation (Supplemental Fig.…”
mentioning
confidence: 99%
“…Previously, this technology has been used for production of both ethanol (e.g. Teixeira et al, 1999Teixeira et al, , 2000Kang et al, 2010) and lactic acid (e.g. Patel et al, 2005;Zhu et al, 2007).…”
Section: Simultaneous Saccharification and Co-fermentation (Sscf)mentioning
confidence: 99%
“…Co-cultures or microbial consortia may also be utilized in the CBP systems as the third methodology. Brandon et al 2011Kang et al, 2010Kim et al, 2008Geddes et al, 2011Nieves et al, 2011Mullinnix, 2014Yang et al, 2014Jin et al, 2014 Jin et al 2012aOhgren et al 2006Wang et al, 2014aYasuda et al, 2014Zhu et al, 2014Fonseca et al, 2011Teixeira et al, 1999Jin et al, 2010Tang et al, 2011Zhang (J) et al, 2009Kim and Lee, 2005Zhang et al, 2012bYu et al, 2014Moreno et al, 2013Erdei et al, 2013aBallesteros et al, 2013Geddes et al, 2013Turhan et al, 2014Lan et al, 2013Hargreaves et al, 2013Alvira et al, 2011Olofsson et al, 2010a . In co-culture systems, saccharolytic and ethanologenic microorganisms are co-cultured to enhance efficient saccharification and fermentation in one pot.…”
Section: Strategies To Design Ideal Microorganisms For Cbpmentioning
confidence: 99%
“…However, the commercial application of technology for transforming high carbohydrate content of the sludge into the value added products through SSF can support to meet the environmental and economic concerns. Using the sludge which generally contains low lignin content has been proven to be extremely proficient for its bioconversion into ethanol [72,73]. Moreover, it was also found quite successful for the ethanol production at commercial scale as they get the sludge as a waste free of cost since the sludge have no market value, pre-treatment can be eliminated and simultaneously the issue of the sludge disposal is also being compromised with no cost.…”
Section: Pulp and Paper Industrymentioning
confidence: 99%